2019
DOI: 10.1039/c9py00241c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of 1,4-cis-polyisoprene–polypeptide hybrids with different architectures

Abstract: 2-Pot synthesis of a number of amino-hydroxy macroinitiators for living NCA ROP allowed to obtain polyisoprene–polypeptide hybrids of different architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…At the later stage of cross-linking, when the concentration of remaining amines (primary and secondary) is already low, viscosity and cross-linked medium prevent free diffusion of unreacted components, and side reactions corresponding to the peak at 199 °C (Figure ) become more preferable. Hydroxy groups linked to a tertiary amine by two carbon atoms are known to be stronger nucleophiles than other aliphatic alcohols due to hydrogen bonding with nitrogen atom. , That is why it can be suggested that OH-groups formed at the first stage of reaction may react with remaining epoxy groups (Scheme , OH- ring opening). The previous tertiary amine is also a nucleophile which can also participate in epoxide ring-opening forming an ammonium salt .…”
Section: Results and Discussionmentioning
confidence: 99%
“…At the later stage of cross-linking, when the concentration of remaining amines (primary and secondary) is already low, viscosity and cross-linked medium prevent free diffusion of unreacted components, and side reactions corresponding to the peak at 199 °C (Figure ) become more preferable. Hydroxy groups linked to a tertiary amine by two carbon atoms are known to be stronger nucleophiles than other aliphatic alcohols due to hydrogen bonding with nitrogen atom. , That is why it can be suggested that OH-groups formed at the first stage of reaction may react with remaining epoxy groups (Scheme , OH- ring opening). The previous tertiary amine is also a nucleophile which can also participate in epoxide ring-opening forming an ammonium salt .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This reaction was performed as already described. 8 Briefly, 10 g of NR were cut into small pieces and dissolved overnight at RT in 500 mL of THF in round-bottom flask under stirring. In parallel, 550 mg (3.2 mmol) of mCPBA were dissolved in 50 mL of THF, and then added dropwise into the NR solution to epoxidize the PI.…”
Section: Synthesis Of Maleimide End-functionalized Pimentioning
confidence: 99%
“…This reaction was performed under argon atmosphere as already described. 8 Briefly, 6 g of purified PIEG 5500 g mol −1 (equivalent to 1.2 mmol of aldehyde groups) were dissolved in 25 mL of dry THF. Then, 1.02 g (4.8 mmol, 4 eq.)…”
Section: Synthesis Of Maleimide End-functionalized Pimentioning
confidence: 99%
See 2 more Smart Citations